The Effectiveness of Problem Based Learning (PBL) on Intermediate Financial Accounting Subject - Nunuk Suryanti (Dinamika Pendidikan)
This research aims to know the effectiveness of Problem Based Learning (PBL) Model comparing to Drill Model on Intermediate Financial Accounting subject. The research was a quasi-experimental research. Population was four classes of Accounting Education students in the year of 2014/2015 at Faculty of Educational Science and Teaching of Riau Islamic University (UIR). Sample was taken by using purposive sampling. Then, it used Problem Based Learning (PBL) at experimental class and Drill Model at controlled class. Data was collected by using interview, observation, and tests (pre-test and post-test). Moreover, data were analyzed by using independent sample test. Findings show that there is no any difference of learning outcomes between students who taught by Problem Based Learning (PBL) Model and Drill Model on Intermediate Financial Accounting.